N- and O-glycan cell surface protein modifications associated with cellular senescence and human aging. Issue 1 (December 2016) - Itakura, Yoko; Sasaki, Norihiko; Kami, Daisuke; Gojo, Satoshi; Umezawa, Akihiro; Toyoda, Masashi
Abstract Background Glycans play essential roles in biological functions such as differentiation and cancer. Recently, glycans have been considered as biomarkers for physiological aging. However, details regarding the specific glycans involved are limited. Here, we investigated cellular senescence- and human aging-dependent glycan changes in human diploid fibroblasts derived from differently aged skin donors using a lectin microarray. Results We found that α2-6sialylated glycans in particular differed between elderly- and fetus-derived cells at early passage. However, both cell types exhibited sequentially decreasing α2-3sialylatedO -glycan structures during the cellular senescence process and showed similar overall glycan profiles. Conclusions We observed a senescence-associated decrease in sialylation and increase in galactose exposure. Therefore, glycan profiling using lectin microarrays might be useful for the characterization of biomarkers of aging.